2019
DOI: 10.18632/oncotarget.26541
|View full text |Cite
|
Sign up to set email alerts
|

Immune checkpoint inhibitors in EGFR-mutation positive TKI-treated patients with advanced non-small-cell lung cancer network meta-analysis

Abstract: Non-Small Cell Lung Cancer (NSCLC) patients with Epidermal Growth Factor Receptor (EGFR) mutation benefit from a first line of treatment with tyrosine kinase inhibitors (TKIs). After progression, the choice of treatment is between chemotherapy and immune checkpoint inhibitors, but the role of EGFR mutation in the response to immunotherapy is still unclear. A network meta-analysis was performed and 4 randomized trials comparing immune checkpoint inhibitors versus chemotherapy were identified. A Bayesian network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 19 publications
2
21
1
1
Order By: Relevance
“…We subsequently investigated this biomarker in a cohort of 36 EGFR-mutated patients. Previous studies have reported that EGFR-mutated NSCLC patients are poor responders to nivolumab [13,41]. All 36 patients exhibited baseline sCombo positivity due to a constant expression of sPD-L1, thus, these results suggest that baseline sCombo positivity may not only be prognosic, but most importantly could be predictive of failure of nivolumab therapy in NSCLC patients.…”
Section: Discussionsupporting
confidence: 51%
See 3 more Smart Citations
“…We subsequently investigated this biomarker in a cohort of 36 EGFR-mutated patients. Previous studies have reported that EGFR-mutated NSCLC patients are poor responders to nivolumab [13,41]. All 36 patients exhibited baseline sCombo positivity due to a constant expression of sPD-L1, thus, these results suggest that baseline sCombo positivity may not only be prognosic, but most importantly could be predictive of failure of nivolumab therapy in NSCLC patients.…”
Section: Discussionsupporting
confidence: 51%
“…In our control cohort of 36 NSCLC EGFR-mutated patients, all patients exhibited a constant baseline expression of sPD-L1. Given that EGFR-mutated lung cancers are known to be resistant to anti-PD1 therapies [41,56], these findings support a deleterious effect of sPD-L1 expression on nivolumab efficacy in NSCLC patients. Interestingly, in a previous study a similar trend has been observed among NSCLC patients treated with another anti-PD1, pembrolizumab combined with low doses of chemotherapy.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…87 Checkpoint inhibitor therapy is generally ineffective in this patient population. 88,89 Enrollment in clinical trials is ideal and should be strongly considered for these patients.…”
Section: Evolving Treatment Paradigm For Egfr Positive Metastatic Nsclcmentioning
confidence: 99%